Derivation of Sago Processed Food in Yupaet MSMEs - Resdati, Resdati; Yusuf, Yusmar; Sidiq, Rd Siti Sofro; Bahagiana, Berkah; Lestari, Niken Fujia; Ningsih, Ike Rahma (Journal of Applied Business and Technology, 2024)
This research aims to investigate the derivation process of processed sago food carried out by Yupaet Micro, Small and Medium Enterprises (MSMEs). Sago, which is one of the superior products in the Meranti Islands Regency area, has the potential to be developed into various processed food products that have added value. The research method used is descriptive qualitative. Researchers observed and analyzed the production processes and innovations carried out by Yupaet MSMEs in processing sago into various processed foods, especially sago noodles. The data obtained was collected through interviews, observation, and documentation. Data analysis was carried out in stages, namely reduction, presentation, and conclusion. The research results showed that Yupaet MSMEs have an understanding of the techniques and processes for processing sago into various processed foods and have succeeded in deriving processed sago foods well, thereby producing processed food products that have added value. One of the processed sago foods that Yupaet MSMEs have successfully made is the first instant sago noodles in Riau with the product name Mie Sago Boedjang.